Dynamics and Half-Life of Cell-Free DNA After Exercise: Insights from a Fragment Size-Specific Measurement Approach - Ryutaro Yamamoto; Hiroshi Asano; Ryo Tamaki; Yoshihiro Saito; Ami Hosokawa; Hidemichi Watari; Takeshi Umazume (Diagnostics)
Background: Cell-free DNA (cfDNA) is present in healthy individuals but is elevated in those undergoing physical exertion, trauma, sepsis, and certain cancers. Maintaining cfDNA concentrations is vital for immune homeostasis and preventing inflammatory responses. Understanding cfDNA release and clearance is essential for using cfDNA as a biomarker in clinical diagnostics. We focused on the fragment size of cfDNA and investigated cfDNA dynamics and half-life, particularly the 100–250 base pair fragments. Methods: Healthy, adult men (n = 5; age 40 ± 4.1 years) were subjected to a 30 min treadmill exercise. Blood samples were collected at 0, 5, 10, 15, 30, and 60 min post-exercise using PAXgene® Blood ccfDNA tubes to stabilize and prevent nuclease-mediated cfDNA degradation and minimize genomic DNA contamination risk. The cfDNA concentration was measured using an electrophoresis-based technique (4150 TapeStation system) to quantify the concentration based on cfDNA fragment size. Results: The results showed a cfDNA half-life of 24.2 min, with a transient increase in 100–250 base pair cfDNA fragments post-exercise, likely due to nuclease activity. These levels rapidly reverted to the baseline within an hour. Conclusions: The rapid clearance of cfDNA underscores its potential as a biomarker for real-time disease monitoring and the evaluation of treatment efficacy. This study is expected to standardize cfDNA investigations, enhancing diagnosis and treatment monitoring across various disease conditions.